A city on the edge: the political ecology of urban green space. (October 2021) - Cobbinah, Patrick Brandful; Nyame, Valentina
African cities, faced with rapid urbanization and haphazard land use practices, struggle to address their fast-declining urban green space (UGS). Yet the spatial extent of UGS, and the influence of city planning legislation and frameworks, remains largely unexplored. Using a case study of Kumasi, Ghana, this study draws on mixed methods to address three research questions: (i) How did Kumasi's UGS evolve from 1991 to 2019? (ii) How do city planning, legislation and the regulatory framework influence UGS management? (iii) What is the land governance institutional culture for managing UGS? Findings from the spatial analysis indicate a loss of over 80 per cent in Kumasi's UGS between 1991 and 2019. Although unplanned urbanization, poor urban planning and political interference were frequently discussed as contributory factors, the foundational cause was found to lie in the complex and conflicting relationship between land governance agencies. This situation has resulted in the absence of a culture of coordination with regard to urban development, particularly towards UGS.